PERCENTAGE OF WEIGHT INCREASE IN EUROPEAN SPRUCE WOOD (Picea Abies.Mill), IMPREGNATED WITH PОLYURETHANE AND ACRYLIC COATINGS - Nikola Mihajlovski; Konstantin Bahchevandjiev; Mitko Nacevski (Faculty of Design and Technologies of Furniture and Interior-Skopje, 2013)
Capillary absorption - impregnating the wood with filmogenic materials, represents a possible method for surface modification of the wood. By application of double vacuum process, polymeric filmogenic materials are incorporated into the cellular and intracellular cavities of the wood surface layers. The Weight Percent Gain - WPG is significantly larger than with classically coated wood. The progress rate of WPG of two dimensions of test pieces in the impregnation process with polyurethane coating is 11.39% and 36.03%, and in impregnation with acrylic coating it is 10.60% and 28.70%. The differences in impregnated wood with polyurethane and acrylic coating are not statistically significant.
Keywords: impregnation - capillary absorption, European spruce, polyurethane coatings, acrylic coatings, the Weight Percent Gain